Ownership feature and firm performance via corporate innovation performance: Does it really matter for Vietnamese SMEs? - Nguyen, Dung (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to investigate the simultaneous relationship among ownership concentration, innovation and firm performance of the small- and medium-sized enterprises (SMEs) in Vietnam during the 2011–2015. By employing a Conditional Mixed Process (CMP) model, the findings show that: there is no impact of ownership concentration on innovation, but it has a positive impact on sales growth; innovation positively affects firm performance; and there exists a positively reverse causality from sales growth to innovation. Design/methodology/approach In this study, the authors propose the adaption of CMP model (Roodman, 2011). The nature of the first stage dependent variable – Innovation – is a binary one while the dependent variable Performance is continuous. Therefore, a model that can adapt the binary nature of the dependent variable and perform the estimation of a system of equations such as CMP model is preferred. The CMP framework is substantially that of seemingly unrelated regression, but with application in a larger scope. This approach is based on a “simulated maximum likelihood method” suggested by Geweke–Hajivassiliou–Keane algorithm. Findings By applying CMP method, this study examines the simultaneous relationship among ownership concentration, innovation and firm performance of the SMEs in Vietnam from 2011 to 2015. The findings indicate that: there is no impact of ownership concentration on innovation, but it has a positive impact on sales growth; innovation positively affects firm performance; and there exists a positively reverse causality from sales growth to innovation. Research limitations/implications In spite of the efforts to explore the simultaneous relationship among ownership concentration, innovation and firm performance of the SMEs in Vietnam, the study still has some limitations which are promising further research directions. First, the SME surveys by Central Institute for Economic Management do not have much information about other types of ownership including state-owned and foreign ownership. Therefore, possible further studies with richer data sets may explore the impacts of different types of ownership on firm innovation and performance. Second, other types of innovation such as organizational innovation, marketing innovation can also be investigated in further studies in a richer data set for the case of Vietnam SMEs. Originality/value The findings show that: there is no impact of ownership concentration on innovation, but it has a positive impact on sales growth; innovation positively affects firm performance; and there exists a positively reverse causality from sales growth to innovation. The policy implications insist on facilitating SMEs with easier access to capital via loans with preferred interest or trust loans without collateral, training programs for the labor force and SME leaders, and reduction of unnecessary administrative procedure.